Prevalence and predictors of post-stroke mood disorders: A meta-analysis and meta-regression of depression, anxiety and adjustment disorder - Mitchell, Alex J.; Sheth, Bhavisha; Gill, John; Yadegarfar, Motahare; Stubbs, Brendon; Yadegarfar, Mohammad; Meader, Nick (General hospital psychiatry, 2017)
To ascertain the prevalence and predictors of mood disorders, determined by structured clinical interviews (ICD or DSM criteria) in people after stroke. Major electronic databases were searched from inception to June 2016 for studies involving major depression (MDD), minor depression (MnD), dysthymia, adjustment disorder, any depressive disorder (any depressive disorder) and anxiety disorders. Studies were combined using both random and fixed effects meta-analysis and results were stratified as appropriate. Depression was examined on 147 occasions from 2days to 7years after stroke (mean 6.87months, N=33 in acute, N=43 in rehabilitation and N=69 in the community/outpatients). Across 128 analyses involving 15,573 patients assessed for major depressive disorder (MDD), the point prevalence of depression was 17.7% (95% CI=15.6% to 20.0%) 0.65 analyses involving 9720 patients determined MnD was present in 13.1% in all settings (95% CI=10.9% to 15.8%). Dysthymia was present in 3.1% (95% CI=2.1% to 5.3%), adjustment disorder in 6.9% (95% CI=4.6 to 9.7%) and anxiety in 9.8% (95% CI=5.9% to 14.8%). Any depressive disorder was present in 33.5% (95% CI=30.3% to 36.8%). The relative risk of any depressive disorder was higher following left (dominant) hemisphere stroke, aphasia, and among people with a family history and past history of mood disorders. Depression, adjustment disorder and anxiety are common after stroke. Risk factors are aphasia, dominant hemispheric lesions and past personal/family history of depression but not time since stroke. Meta-regression on major depression and time since stroke. [Display omitted] •We conducted a meta-analysis of 128 studies involving 15,573 patients follow a stroke.•The point prevalence of major depression was 17.7% (95% CI=15.6% to 20.0%).•Any form of depression (ADD) was present in 33.5% (95% CI=30.3% to 36.8%).•Risk of depression was higher after left hemisphere stroke, aphasia, and past history of mood disorders.